Analysis of reaction pathways and catalytic sites on metal-free porous biochar for persulfate activation process. (December 2020) - Zou, Jiajing; Yu, Jiangfang; Tang, Lin; Ren, Xiaoya; Pang, Ya; Zhang, Hao; Xie, Qingqing; Liu, Yani; Liu, Haoyu; Luo, Ting
Abstract: To develop a metal-free biochar with high and inherent catalytic activity towards refractory and highly toxic contaminants in advanced oxidation processes, it is necessary to explore its reaction pathways and responsible catalytic sites. Herein, a metal-free biochar derived from corn cob (CCBC) was prepared and used for reaction pathway analysis during peroxydisulfate (PDS) activation. The pyrolysis temperature played an important role for regulating the biochar structure and properties, and CCBC obtained at 800 °C showed the best adsorption capacity and catalytic activity towards five typical organic pollutants, including 2, 4-dichlorophenol, Tetracycline hydrochloride, Ciprofloxacin, Methyl orange and Rhodamine B, due to its richer pore and defect structure. Further treatment of pharmaceutical wastewater demonstrated the good efficiency and potential of this metal-free catalyst for practical application. Radical (58% contribution) and non-radical (42% contribution) pathways were both found in CCBC/PDS system. More importantly, further redox experiments manifested that the carbon framework (defects, sp 2 -hybrid carbon, etc.) only made a contribution to the free radical pathway, while the ketone group (CO) of CCBC was proved to be mainly responsible for the non-radical pathway, namely the generation of singlet oxygen ( 1 O2 ). Graphical abstract: Image 1 Highlights: Porosity and defects facilitate adsorption and catalytic performance. Radical and non-radical pathways were both found in the system. C=O and defects on the carbon framework were two key active sites. Carbon frame only contributed to free radicals and 1 O2 was mainly generated by C=O. CCBC was effective to pharmaceutical wastewater and organics degradation.